2016
DOI: 10.1080/00140139.2016.1235233
|View full text |Cite
|
Sign up to set email alerts
|

Grip force and force sharing in two different manipulation tasks with bottles

Abstract: Grip force and force sharing during two activities of daily living were analysed experimentally in 10 right-handed subjects. Four different bottles, filled to two different levels, were manipulated for two tasks: transporting and pouring. Each test subject's hand was instrumented with eight thin wearable force sensors. The grip force and force sharing were significantly different for each bottle model. Increasing the filling level resulted in an increase in grip force, but the ratio of grip force to load force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…During grasping, the coordination of forces and moments among digits is affected by the locations (Li et al, 1998; Marneweck et al, 2016; Zatsiorsky et al, 2003) and the number (Budgeon et al, 2008) of fingers contacting as well as object properties and task features (Cepriá-Bernal et al, 2017). Previous studies showed that the location of each digit during natural grasp is varied precisely according to the shape and content of the bottle and the grasping task (Crajé et al, 2011; Lukos et al, 2007; Marneweck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During grasping, the coordination of forces and moments among digits is affected by the locations (Li et al, 1998; Marneweck et al, 2016; Zatsiorsky et al, 2003) and the number (Budgeon et al, 2008) of fingers contacting as well as object properties and task features (Cepriá-Bernal et al, 2017). Previous studies showed that the location of each digit during natural grasp is varied precisely according to the shape and content of the bottle and the grasping task (Crajé et al, 2011; Lukos et al, 2007; Marneweck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bernal et al measured the grip force in different subjects through wearable capacitive pressure sensors in the fingers while performing a daily-life activity such as lifting a half-full 1-l bottle. The mean grip strength was 18.6 N [ 15 ]. Since every 10 N of grasp force transmits 26.4 N through the radius in the axial direction [ 16 ], the axial compression is approximately 49 N. Based on these estimates, we used 50 N for axial compression.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo loading conditions in the human DRUJ have not been completely determined. Bernal et al [23] found that the mean grip force was 18.6 N when performing a daily life activity by measuring different subjects through wearable capacitive pressure sensors in the ngers. Putnam et al [24] reported that each 10 N of grip force would transmit 26 N of force through the distal ulna metaphysis in the wrist neutral position.…”
Section: Loading Force Settingsmentioning
confidence: 99%